Generalized Variability Orderings among Nonnegative Fuzzy Random Variables - S. Ramasubramanian; P. Mahendran (Abstract and Applied Analysis)
The variability ordering for more and less variables of fuzzy random variables in terms of its distribution function is defined. A property of new better than used in expectation (NBUE) and new worse than used in expectation (NWUE) is derived as an application to the variability ordering of fuzzy random variables. The concept of generalized variability orderings of nonnegative fuzzy random variables representing lifetime of components is introduced. The <P domination is a generalized variability ordering. We proposed an integral inequality to the case of fuzzy random variables using <P ordering. The results included equivalent conditions which justify the generalized variability orderings.